Rwanda : Fourth Review of the Policy Coordination Instrument and Request of an Extension of the Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report, 2021)
Recent economic developments. Despite a sizeable policy response, the COVID-19 pandemic continues to impact Rwanda's economy and social fabric, with output contracting by 3.4 percent in 2020. The vaccine rollout is expected to help counter the pandemic and support the economic recovery, but risks remain elevated. While progress was made in several reform areas, some envisaged reforms are being delayed. The authorities requested the extension of the program by one year to make progress on ongoing reforms and policies to support the economic recovery and meet their fiscal consolidation and debt objectives. Rwanda received debt relief under the third tranche of the Catastrophe Containment and Relief Trust (CCRT).